Longitudinal program evaluation of an inter-institutional mentorship network for pediatric rheumatology using a quality improvement framework - Kristen Hayward; Alexi Grom; Eyal Muscal; Peter A. Nigrovic; Kelly A. Rouster-Stevens; Kaveh Ardalan; Linda Hiraki; L. Nandini Moorthy; for the A. C. R./CARRA Mentoring Interest Group (BMC, 2024)
Abstract Background The American College of Rheumatology (ACR)/Childhood Arthritis and Rheumatology Research Alliance (CARRA) Mentoring Interest Group (AMIGO) is an inter-institutional mentorship program launched to target mentorship gaps within pediatric rheumatology. Initial program evaluation indicated increased mentorship access. Given the small size of the pediatric rheumatology workforce, maintaining a consistent supply of mentors was a potential threat to the longevity of the network. Our aims were to: (i) describe the sustainability of AMIGO over the period 2011-2018, (ii) highlight ongoing benefits to participants, and (iii) describe challenges in the maintenance of a mentorship network. Methods A mixed-methods approach centered on a quality improvement framework was used to report on process and outcomes measures associated with AMIGO annual cycles. Results US and Canada Pediatric rheumatology workforce surveys identified 504 possible participants during the time period. As of fall 2018, 331 unique individuals had participated in AMIGO as a mentee, mentor or both for a program response rate of 66% (331/504). Survey of mentees indicated high satisfaction with impact on general career development, research/scholarship and work-life balance. Mentors indicated increased sense of connection to the community and satisfaction with helping mentees despite limited perceived benefit to their academic portfolios. Based on AMIGO's success, a counterpart program for adult rheumatology, Creating Adult Rheumatology Mentorship in Academia (CARMA), was launched in 2018. Conclusions Despite the challenges of a limited workforce, AMIGO continues to provide consistent access to mentorship opportunities for the pediatric rheumatology community. This experience can inform approaches to mentorship gaps in other academic subspecialties.